Utilizing bioaugmentation to improve performance of a two-phase AnMBR treating sewage sludge. Issue 10 (28th April 2020) - Martin-Ryals, Ana D.; Schideman, Lance C.; Ong, Matthew
ABSTRACT: Bioaugmentation in the acid-phase of a two-phase anaerobic membrane bioreactor (AnMBR) treating primary sludge was investigated as a means for targeting and improving hydrolysis and acetogenesis. Bioaugmentation was carried out using a proprietary bioculture blend containing a mixture of hydrolytic, acidogenic, and acetogenic microorganisms. This mixture was added on its own and in combination with recycled anaerobic sludge from the methane-phase of the AnMBR. Both bioaugmentation strategies had a positive effect on overall hydrolysis (25–38%), and acid-phase acetic acid generation (31–52%) compared to operation without bioaugmentation. This led to subsequent increases in average methane production (10–13%), and greater average solids reduction (25–55%). Microbial community analysis using 16S Illumina MiSeq generated sequences revealed increased relative abundance of Acetobacter and Syntrophomonas species in bioaugmented communities, suggesting these to be key players in improvements in process performance. However, in general the relative abundance of bioaugmented microorganisms within bioaugmented communities was relatively low, highlighting the need to optimize the bioculture composition and dosage. Overall, bioaugmentation was found to benefit the conversion of primary sludge to methane, when initial solubility was relatively low. Future work should optimize the bioculture composition and dosing strategy to improve its effectiveness and long-term stability, and minimize associated operating costs. GRAPHICAL ABSTRACT: